Scientist Goes to Village’ programme aims to enrich STEM - Siti Nurfarmy, Ibrahim (2019)
The Renaissance of Science Educators (ROSE) community organised the ‘Scientist Goes to Village’ programme at Kampung Kuala Wau, Maran on January 2, 2019.